Labor Productivity of the Silk Weaving Industry: A Case Study in Pakkanna Village, Wajo Regency - Iskandar, Ahmad Syarief; Ilham, Ilham; Jisal, Muh. (Jurnal Office, 2019)
This study aims to determine the factors that influence labor productivity in the silk weaving industry with a case study of weaving workers in Pakkanna Village, Tanasitolo District, Wajo Regency. The quantitative research method is used in this study using multiple regression analysis to examine the effect of age, length of work, and wages on labor productivity in the silk weaving industry. Data were collected using a questionnaire involving 39 respondents from the silk weaving industry in Pakkanna Village, Tanasitolo District, Wajo Regency. The test results show that simultaneously, the variables of age, length of work, and wages significantly affect labor productivity in the silk weaving industry. On the other hand, the partial test results show that the age variable has no significant effect on labor productivity, and the variable length of work and wages have a significant effect on the labor productivity of the weaving industry. The recommendations in this study are addressed to the government and industry players to guide training to silk weaver workers so that productivity and quality can be increased and pay attention to their welfare. In addition, the government and industry players are expected to continue to work together to promote and develop the silk industry in Wajo Regency.